2003
DOI: 10.1042/bj20030323
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thermal denaturation of Thermus aquaticus and Escherichia coli type 1 DNA polymerases

Abstract: Thermal denaturations of the type 1 DNA polymerases from Thermus aquaticus (Taq polymerase) and Escherichia coli (Pol 1) have been examined using differential scanning calorimetry and CD spectroscopy. The full-length proteins are single-polypeptide chains comprising a polymerase domain, a proofreading domain (inactive in Taq) and a 5' nuclease domain. Removal of the 5' nuclease domains produces the 'large fragment' domains of Pol 1 and Taq, termed Klenow and Klentaq respectively. Although the high temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 36 publications
2
45
0
1
Order By: Relevance
“…When using Taq DNA pol, the PCR yield roughly triples for every 10 °C increase until it reaches an optimum temperature of 72-75 °C (Innis et al, 1988). In retrospect, this is a curious observation since it has recently been shown that this enzyme unfolds only when the temperature reaches 95 °C (Karantzeni et al, 2003). This enzyme's long half-life at the PCR melting temperature is the consequence of its very high barrier to unfolding.…”
Section: Introductionmentioning
confidence: 99%
“…When using Taq DNA pol, the PCR yield roughly triples for every 10 °C increase until it reaches an optimum temperature of 72-75 °C (Innis et al, 1988). In retrospect, this is a curious observation since it has recently been shown that this enzyme unfolds only when the temperature reaches 95 °C (Karantzeni et al, 2003). This enzyme's long half-life at the PCR melting temperature is the consequence of its very high barrier to unfolding.…”
Section: Introductionmentioning
confidence: 99%
“…In principal, fraying of the duplex ends should be more prevalent at this reaction temperature, which should increase the propensity for partitioning of the (À) strand into the exonuclease domain of KF. However, given that a population of KF would exist in a partially unfolded state at 508C (T m ¼ 458C at pH 7.5) (Karantzeni et al, 2003), selective heat inactivation of the exonuclease domain responsible for KF-mediated removal of the 3 0 -IHA may be occurring while the polymerase domain remains intact (Bailey et al, 2004).…”
Section: Kf Removes the 3 0 -Iha From Model Atsmentioning
confidence: 99%
“…5(b), the melting profile was typical. A gradual increase in ellipticity at 220 nm was observed for Bh-MutT up to $323 K, followed by a more rapid increase in ellipticity that leveled off at $335 K. Visual inspection of the sample after heating to 353 K showed evidence of precipitation, indicating that the unfolding was irreversible, and consequently the CD data could not be analyzed thermodynamically (Karantzeni et al, 2003). A quantitative estimation of the T m for this transition was still possible by assuming a two-state model and taking a first derivative of the curve in Fig.…”
Section: Circular Dichroism Profile and Thermal Stability Of Bh-muttmentioning
confidence: 99%
“…Usually, the ellipticity at a specific wavelength increases with increasing temperature as the protein unfolds and a melting temperature, T m , may be estimated for the transition between a structured and an unstructured state (Karantzeni et al, 2003). However, it has recently been observed that the thermal melt for the Nudix hydrolase DR_0079 from the bacterium Deinococcus radiodurans displays the opposite behavior, suggesting an increase in ordered structural communications structure with an increase in temperature (Buchko, 2010).…”
Section: Circular Dichroism Profile and Thermal Stability Of Bh-muttmentioning
confidence: 99%